Strategic Management of Early Education Section and Islamic Boarding Schools in Improving Managerial Competence of The Principal of Education Equality in Salafiyah Islamic Boarding Schools (PKPPS) at Kabupaten Bekasi - Yuniarto, Evan; Suharyat, Yayat; Diyah (Proceeding International Conference on Education, 2023)
This study aims to find out and analyze how the strategic management of the Diniyah Education and Islamic Boarding School sections in improving the managerial competence of the head of the Equality Education madrasah at the Salafiyah Islamic Boarding School (PKPPS) throughout Bekasi Regency". This study used qualitative research. Data is taken through interviews, observations and documents obtained in the field. The results of this study are known that there are 70% of heads of Equality Education madrasahs at Salafiyah Islamic Boarding Schools (PKPPS) low in managerial competence even though this competence is a very important requirement in managing Equality Education madrasahs at Salafiyah Islamic Boarding Schools owned by Salafiyah Islamic Boarding Schools. Then this matter must immediately get attention and solutions.  To overcome this condition, it must be studied or researched so that it can be a material for the proposal of the Religious Office program in Bekasi Regency. So that it can be budgeted in the Regional Budget (APBD). Then there is a need for strategic management by the Diniyah Education section and Islamic Boarding School so that they are able to design guidelines for planning, implementation and control of the managerial ability improvement program of the head of the Equality Education madrasah at the Salafiyah Islamic Boarding School (PKPPS) in Bekasi district.